ADSCs Promote Tenocyte Proliferation by Reducing the Methylation Level of lncRNA Morf4l1 in Tendon Injury - Zhao, Haibo; Chen, Wei; Chen, Jinli; Qi, Chao; Wang, Tianrui; Zhang, Jing; Qu, Di; Yu, Tengbo; Zhang, Yingze (Frontiers in Chemistry, 2022)
Objective: Tendons are a crucial component of the musculoskeletal system. The healing of tendon injuries is still a challenge. In recent years, adipose-derived mesenchymal stem cells (ADSCs) have been increasingly used for tissue regeneration, but the underlying mechanism of tendon injury still remains unclear. Methods: High-throughput sequencing was used to identify a novel lncRNA, whose expression was significantly decreased in injured tendon compared with normal tendon. Furthermore, pyrosequencing, nuclear-cytoplasmic separation, FISH assay and qRT-PCR analysis were used to verify the level of lncRNA methylation in the injured tenocytes. lncRNA was confirmed to promote the proliferation of tenocytes by flow cytometry, wound healing assay, qRT-PCR, and western blot, and the target gene of lncRNA was predicted and verified. To confirm that ADSCs could repair injured tendons, ADSCs and injured tenocytes were co-cultured in vitro, and ADSCs were injected into injured tendons in vitro, respectively. Results: The lncRNA Morf4l1 promoter methylation in injured tendons led to down-regulation of its expression and inhibition of tenocyte proliferation. LncRNA Morf4l1 promoted the expression of TGF-β2 by targeting 3'U of miR-145-5p. After co-cultured ADSCs and injured tenocytes, the expression of lncRNA Morf4l1 was up-regulated, and the proliferation of injured tenocytes in vitro was promoted. The ADSCs were injected into the injured tendon to repair the injured tendon in vivo. Conclusion: This study confirmed that ADSCs promoted tendon wound healing by reducing the methylation level of lncRNA Morf4l1.